At the crossroads : Indians and empires on a mid-Atlantic frontier, 1700-1763 - Merritt, Jane T. (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia, by the University of North Carolina Press, 2003)
Examining interactions between native Americans and whites in eighteenth-century Pennsylvania, Jane Merritt traces the emergence of race as the defining difference between these neighbors on the frontier. Before 1755, Indian and white communities in Pennsylvania shared a certain amount of interdependence. They traded skills and resources and found a common enemy in the colonial authorities, including the powerful Six Nations, who attempted to control them and the land they inhabited. Using innovative research in German Moravian records, among other sources, Merritt explores the cultural prac.